Awareness of fertility and reproductive aging in women seeking oocyte cryopreservation, reproductive aged controls, and female health care professionals: A comparative study. (February 2019) - Dundar Akın, Oznur; Boza, Aysen; Yakin, Kayhan; Urman, Bulent
Abstract: Objective: To compare the awareness of fertility and reproductive aging in women seeking oocyte cryopreservation (OC) with age matched controls. Study design: In this cross-sectional comparative study, women who were candidates for OC due to impending oocyte depletion (n = 81) were compared to age matched reproductive aged women (RAW) (n = 91) and female healthcare professionals (FHP) (n = 82) in terms of awareness about fertility and reproductive aging and knowledge about OC. A study specific 18-item questionnaire was constructed on the basis of previous research on OC and fertility. Results: Awareness of fertility and reproductive aging was similar among groups. The majority of study population was quite realistic of women's most fertile age period whereas they were fairly optimistic about the age that a woman may lose her ability to conceive, monthly fecundity rate, and estimated in vitro fertilization treatment success. OC candidates and FHP were more realistic compared to RAW regarding the age after which the chances of conception is severely diminished (p = 0.005). When the knowledge on OC and willingness to preserve fertility in the future were asked to FHP and RAW, 90% stated that they were aware of the option (93% in FHP versus 88% in RAW, p = 0.006). However, they lacked detailed information about OC and they were unlikely to consider it in the future. Conclusions: Women seeking OC did not appear to have a better awareness of reproductive ageing compared to the general female population. The results of this study highlight the need for additional awareness campaigns and education on both personal and professional levels.